Amblyopia treatment of adults with dichoptic training using the virtual reality oculus rift head mounted display: preliminary results - Žiak, Peter; Holm, Anders; Halička, Juraj; Mojžiš, Peter; Piñero, David P (BMC ophthalmology, 2017)
Background The gold standard treatments in amblyopia are penalizing therapies, such as patching or blurring vision with atropine that are aimed at forcing the use of the amblyopic eye. However, in the last years, new therapies are being developed and validated, such as dichoptic visual training, aimed at stimulating the amblyopic eye and eliminating the interocular supression. Purpose To evaluate the effect of dichoptic visual training using a virtual reality head mounted display in a sample of anisometropic amblyopic adults and to evaluate the potential usefulness of this option of treatment. Methods A total of 17 subjects (10 men, 7 women) with a mean age of 31.2 years (range, 17–69 year) and anisometropic amblyopia were enrolled. Best corrected visual acuity (BCVA) and stereoacuity (Stereo Randot graded circle test) changes were evaluated after 8 sessions (40 min per session) of dichoptic training with the computer game Diplopia Game (Vivid Vision) run in the Oculus Rift OC DK2 virtual reality head mounted display (Oculus VR). Results Mean BCVA in amblyopic eye improved significantly from a logMAR value of 0.58 ± 0.35 before training to a post-training value of 0.43 ± 0.38 ( p < 0.01). Forty-seven percent of the participants achieved BCVA of 20/40 or better after the training as compared to 30% before the training. Mean stereoacuity changed from a value of 263.3 ± 135.1 before dichoptic training to a value of 176.7 ± 152.4 s of arc after training ( p < 0.01). A total of 8 patients (47.1%) before dichoptic treatment had unmeasurable stereoacuity while this only occurred in 2 patients (11.8%) after training. Conclusions Dichoptic training using a virtual reality head mounted display seems to be an effective option of treatment in adults with anisometropic amblyopia. Future clinical trials are needed to confirm this preliminary evidence. Trial registration Trial ID: ISRCTN62086471 . Date registered: 13/06/2017. Retrospectively registered